Outcomes of paediatric patients with acquired aplastic anaemia treated with immunosuppressive therapy at two Johannesburg Hospitals - Van der Nest, Alison (My University, 2020)
Background Aplastic anaemia (AA) is a life-threatening disorder of bone marrow failure, due to an autoimmune destruction of stem cells in the bone marrow. Treatment options include haematopoietic stem cell transplantation (HSCT) and immunosuppressive therapy (IST). Most frequently, IST is used for treatment of AA in South Africa as HSCT is often unavailable. This study describes the population of paediatric patients with acquired AA in South Africa and determines their response to IST. Methods and materials A retrospective record review was done of patients diagnosed with AA between January 2002 and December 2011 at two Johannesburg centres. Forty-one records were included. The patient demographics are illustrated. The main outcomes reviewed include overall survival, survival with treatment, response to therapy, rate of relapse and progression to clonal disorders and malignancy, and causes of death.Results 61% of patients were male. The median age at diagnosis was 10.1 years. The majority (67%) had severe AA. Overall survival rates were 68% for all patients and 75% for patients treated with IST. 83% of patients received IST (38% one course, 62% two courses). At the six month evaluations, 6% had a complete response, 59% had a partial response and 15% had no response. The relapse rate was 15% and progression to clonal disorder was 5%. Thirteen patients (32%) demised.Conclusion This study demonstrates patient demographics, survival rates and response to IST in keeping with international findings. The use of IST can be justified in this setting when HSCT cannot be provided.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Medicine in Paediatrics to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, 2020